Penggunaan infusum daun ketapang (Terminalia catappa) sebagai bahan anestesi terhadap diferensiasi leukosit dan waktu induktif sedatif ikan nila (Oreochromis niloticus) - Luthfiannisa, Aisyah; Hary Tjahja Soedibya, Petrus; Pramono, Taufik Budhi (Fishery Product Technology Study Program, Yudharta University, Pasuruan, 2024)
Tilapia is one of the leading commodities in fisheries and requires proper handling in the distribution process so that fish do not experience stress and death. One of them is by using anesthesia. Anesthetic ingredients are divided into two, namely natural and artificial, one of the natural ingredients that has the potential as an anesthetic is ketapang leaves because it has flavanoid and alkaloid compounds that are considered capable of providing hypnotic sedative effects and anti-anxiety substances for fish. The study applied 4 treatments (5 ppm; 10 ppm; 15 ppm; and 20 ppm) of ketapang leaf infusum solution with the method used was descriptive qualitative to obtain research conclusions. The results obtained were the use of ketapang leaf infusion was able to increase lymphocyte levels from 42.13-58.15% to 52.35-60.21%. At a concentration of 20 ppm ketapang leaf infusion has the fastest inductive time of 23 minutes 41 seconds with a sedative time of 18 minutes 52 seconds. From these results it can be concluded that ketapang leaf infusion has potential as a natural anesthetic, but other studies are still needed regarding the percentage of content, effective dose and toxicity of ketapang leaf infusion solution on the hematological condition of tilapia.